Customer experience and brand image on loyalty through customer satisfaction of Erigo consumers - Firdaus, Angelika; Rosnani, Titik; Listiana, Erna; Setiawan, Harry; Fitriana, Ana (Institute of Computer Science (IOCS), 2024)
The increasing number of competitors emerging in the market compete to create various product variants and increasingly unique marketing strategies to be liked by consumers, especially in the fashion industry. This research will examine the extent of the influence of customer experience and brand image on customer loyalty through customer satisfaction among Erigo consumers in Indonesia. This type of research is quantitative research with the population in this study being the entire population of Indonesia who use Erigo-branded clothing. The sample in this study is Erigo branded-clothing consumers who have purchased Erigo-branded clothing at least two times and are aged over 18 years. The sampling technique used in this study is nonprobability sampling of 234 respondents. In this study, customer experience and brand image are the independent variables. The intervening variable is customer satisfaction, which is connected to the primary independent variable towards the dependent variable, customer loyalty. The results reveal that customer experience and brand image positively impact on customer loyalty though only the former has significant impact. Besides, both customer experience and brand image have positive and significant influence on customer satisfaction while customer satisfaction is positively and significantly corelated with customer loyalty. The existance of customer satisfaction as the mediating variable even strengthen this impact. Overall, the more experience customers get from purchasing Erigo’s products and the higher brand image Erigo build, the more satisfied and loyal the customers will be.